Salient Beliefs that Influence the Malaysian Engineers Intention to Migrate Abroad - Ramoo, Balu (Border Crossing, 2018)
Malaysia is one of the countries which face serious outflow of high skilled workers. In particular, high levels of brain drain among the engineers in the country has created a critical shortage of highly skilled workers in Malaysia. Migration studies in Malaysia in the past mostly focused on economic and socio-political aspects but migration among engineers received very little attention. The main purpose of this study is to analyse the intention of Malaysian engineers to migrate abroad from a behavioural perspective. The study also intended to identify the engineers salient beliefs about migration that could explain their intentions. The knowledge regarding the beliefs can be useful for policy makers in order to develop behavioural intervention policies to manipulate (i.e. lower) the engineers intention to move abroad. The engineers intention was analysed using the Theory of Planned Behaviour (TPB). Among the three direct predictors in TPB model, the engineers attitude and their subjective norms were significant in explaining the engineers intentions to move abroad. In turn, a number of salient behavioural and normative beliefs were found to be significant in explaining the engineers attitude and subjective norms.